2018
DOI: 10.1007/s11606-018-4705-2
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Addressing Depression and Diabetes Distress in Adults with Type 2 Diabetes

Abstract: People with type 2 diabetes often experience two common mental health conditions: depression and diabetes distress. Both increase a patient's risk for mortality, poor disease management, diabetes-related complications, and poor quality of life. The American Diabetes Association and the U.S. Preventive Services Task Force recommend routine evaluations for these conditions in adults for optimal disease management and prevention of lifethreatening complications. However, barriers exist within primary care and spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
92
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 32 publications
(61 reference statements)
1
92
0
6
Order By: Relevance
“…Emotional stressors associated with having T2DM have been proven to negatively affect a person’s mental and social well-being [ 44 ]. Depression and diabetes distress can reduce control of HbA1c, blood pressure, and cholesterol, treatment adherence, and overall health among patients with type 2 diabetes [ 45 ]. Medication adherence, disease severity, and depression were also found to be closely correlated with QoL [ 44 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emotional stressors associated with having T2DM have been proven to negatively affect a person’s mental and social well-being [ 44 ]. Depression and diabetes distress can reduce control of HbA1c, blood pressure, and cholesterol, treatment adherence, and overall health among patients with type 2 diabetes [ 45 ]. Medication adherence, disease severity, and depression were also found to be closely correlated with QoL [ 44 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported that in individuals with ischemic heart disease (IHD) the prevalence of postinfarction depression is around 27% which is considerably higher than that observed in the general population [ 6 , 7 , 8 , 9 ]. In the case of type 2 diabetes mellitus (DM), depression is associated with a worse quality of life, lower adhesion to pharmacological treatment, greater metabolic decompensation, and decreased preventive self-care irrespective of the individual’s chronic pathology [ 10 , 11 , 12 ]. Other studies with patients suffering from chronic obstructive pulmonary disease (COPD) have observed depression to be an indicator for emergency room care use and hospitalization due to acute exacerbation of the condition, irrespective of its severity.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with other literature demonstrating decreased disease self-management, increased complications, and increased health care utilization among patients with psychiatric comorbidity. [5][6] We unexpectedly found that hospitalizations associated with epilepsy did not follow this trend, with no significant influence on length of stay and a significantly lower cost in those with psychiatric comorbidity. We believe this may be related to blending of coding accuracy and prioritization when psychiatric and neurologic conditions are both present.…”
Section: Discussionmentioning
confidence: 85%